Effect of local substrates on the development of microtubers of yam (Dioscorea rotundata L.) varieties using the SAH technique - Arlette Adjatin; Sidoine Dedavi; Zaki Bonou-Gbo; Honorine Ogou; Crispus Tossa; Yasmine Bossa; Tiburce Odjo; Jeannette Fakorede; Alexandre Dansi (European Scientific Journal, ESJ, 2025)
The inadequacy of the quantity and quality of production equipment is a major concern for yam production in Benin. Likewise, the new technique of mass production of microtubers is limited by problems related to the supply of the modern substrate. The objective of this study is to identify a local substrate based on plant residues with the potential of those imported (modern substrates) to limit their use in SAH. A control consisting of modern substrate TS3 (SM) and two substrates containing different local residues (100% carbonized peanut shell and 100% carbonized sawdust) were tested on varieties Kouna, Bobo, TDr 9519177, and TDr 8902665. A completely random two-factor bulk experimental design repeated three times was used. The plants were followed through the collection of growth data such as the plants' number, plant height, the number of branches, and the length and width, and then at the harvest, data including the number of microtubers, microtubers diameter, and weight were collected. The results obtained show that the mean of all the parameters considered for the growth and the post-harvest phase are higher with the SM substrate than those of the CA and SB substrates. In addition, discriminating parameters such as the number of microtubers, diameter of microtubers, and weight of microtubers had higher mean values (3.5; 5.37 mm; 037 g) in SB than in CA (2.08; 3.07 mm; 0.19 g), respectively. Plants seeded in the SB substrate showed significant growth gains ranging from 45 to 99% in height and from 35 to 97% in leaf width. Substrate SB, therefore, represents a good medium for the growth and production of microtubers that can replace modern substrate TS3 (SM). Nevertheless, physicochemical characterization and enrichment of the sawdust substrate should be considered to optimize the yield of yam microtubers.